Предмет: Алгебра, автор: davidd13221

Виконайте дії:
(a - 2)/(a ^ 2 - 4) - (a - 2)/(4 - a ^ 2)
(15x - 2)/(10x ^ 2) + (5 + x)/(5x ^ 3)
7/(x ^ 2 + x) + 13/(x + 1)

Ответы

Автор ответа: Artem112
12

Ответ:

\dfrac{a-2}{a^2-4} -\dfrac{a-2}{4-a^2} =\dfrac{2}{a+2}

\dfrac{15x-2}{10x^2} +\dfrac{5+x}{5x^3} =\dfrac{3x^2+2}{2x^3}

\dfrac{7}{x^2+x}+\dfrac{13}{x+1}  =\dfrac{7+13x}{x^2+x}

Решение:

1)

\dfrac{a-2}{a^2-4} -\dfrac{a-2}{4-a^2} =\dfrac{a-2}{a^2-4} +\dfrac{a-2}{a^2-4} =\dfrac{2(a-2)}{a^2-4} =

=\dfrac{2(a-2)}{a^2-2^2} =\dfrac{2(a-2)}{(a-2)(a+2)} =\boxed{\dfrac{2}{a+2}}

2)

\dfrac{15x-2}{10x^2} +\dfrac{5+x}{5x^3} =\dfrac{(15x-2)\cdot x}{10x^3} +\dfrac{(5+x)\cdot2}{10x^3}=

=\dfrac{15x^2-2x}{10x^3} +\dfrac{10+2x}{10x^3}  =\dfrac{15x^2-2x+10+2x}{10x^3} =

=\dfrac{15x^2+10}{10x^3} =\dfrac{5(3x^2+2)}{10x^3}  =\boxed{\dfrac{3x^2+2}{2x^3}}

3)

\dfrac{7}{x^2+x}+\dfrac{13}{x+1} =\dfrac{7}{x^2+x}+\dfrac{13x}{x(x+1)}  =

=\dfrac{7}{x^2+x}+\dfrac{13x}{x^2+x}  =\boxed{\dfrac{7+13x}{x^2+x}  }

Похожие вопросы
Предмет: Химия, автор: kika113
Предмет: Алгебра, автор: koroticnasta1